Deconstructing Disability: Three Episodes of South Park - John Paul Reid-Hresko; D. Kim Reid (Disability Studies Quarterly, 2015)
Through close textual analysis, we examine three South Park episodes to elucidate how they problematize stigmatizing representations and disabling attitudes toward people with physical and cognitive impairments. Using outrageous humor and apparently harmless animation that centers children, the creators expose inconsistencies and injustices typical of the public's responses to disability by contrasting the humanity of disabled persons with cultural assumptions and constructions about them. South Park highlights the pity, charity, and symbolic trope discourses that prevail in mainstream U. S. culture. If the show's general audience can overcome the initial shock value of the language used and positions taken, South Park challenges taken-for-granted and often destructive ways we relate to our environment and our neighbors. In an atmosphere of political correctness that buries representations of difference, South Park stands out as an original, critical voice prompting its audience to question and rethink how our society constructs the social identities of disabled people.